Global pattern of trends in incidence, mortality, and mortality-to-incidence ratio rates related to liver cancer, 1990-2019: a longitudinal analysis based on the global burden of disease study - Maedeh Amini; Mehdi Azizmohammad Looha; Elaheh Zarean; Mohamad Amin Pourhoseingholi (BMC, 2022)
Abstract Background Liver cancer (LC) is considered as one of the most dominant malignant tumors which ranked 4th and in terms of global mortality and incidence, respectively. This work aimed to investigate the global temporal trends in LC mortality-to-incidence ratio (MIR) and its components, with a particular focus on examining long-term effect of human development index (HDI) on these metrics in a 30-year follow-up. Methods The age-standardized LC incidence and mortality data were derived from the global burden of disease (GBD) study 2019. We first leveraged joinpoint piecewise linear regression analysis to ascertain time trends in LC incidence, mortality, and MIR complement [1-MIR] and the average annual percentage change (AAPC) of the rates over the period 1990-2019. Then, the association between the metrics and HDI was explored through longitudinal multilevel models (LMMs). Results The incidence rates paralleled the mortality rates worldwide and they had similar significant monotonic decrementing trends with AAPC values of − 1.10% (95% confidence interval (CI): − 1.40, − 0.90%) and − 1.40% (− 1.50, − 1.30%), respectively from 1990 to 2019. The [1-MIR] rates were around 0 and showed an increasing pattern from 1.70 to 8.10 per 100,000 people (AAPC, 4.90%) at the same period of time. Results from the LMMs displayed that the majority of the variation lies at the country level accounted for about 88% of the total variance. Moreover, our analysis supported that the HDI was negatively associated with either incidence or mortality over time (p < 0.05). Conclusions Our findings highlighted that the global long-term temporal trends of LC incidence and mortality decreased slightly during 1990-2019 which may reflect improved therapeutic strategies and public health interventions. Besides, the low rates of [1-MIR] revealed the five-year relative survival rate was poor implying LC is diagnosed late in its development. Thereby, the policymakers' focus must be on early screening and detection of liver cancer.